Persepsi Mahasiswa Akuntansi Mengenai Dampak Artificial Intelligence terhadap Profesi Akuntan - Restiana Restiana; Depita Anggraini; Rusmianto Rusmianto (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to analyze the influence of knowledge about Artificial Intelligence (AI), awareness of AI, and adaptability skills on accounting students’ perceptions of the impact of AI on the accounting profession. The research employed a quantitative approach using multiple linear regression analysis. The sample size was determined using the Slovin formula with a 10% margin of error, consisting of 100 students from the Tax Accounting and Digital Business Accounting study programs at Lampung State Polytechnic. The results show that, partially, the three independent variables knowledge about AI, awareness of AI, and adaptability skills significantly influence students’ perceptions of the impact of AI on the accounting profession. Simultaneously, these variables also have a significant effect on students’ perceptions. These findings suggest that higher levels of knowledge, awareness, and adaptability among students lead to more positive perceptions of AI’s impact on the accounting profession.